Resting spore formation of aphid‐pathogenic fungus Pandora nouryi depends on the concentration of infective inoculum - Zhi‐Hong Huang; Ming‐Guang Feng (Environmental Microbiology, 2008)
Summary Resting spore formation of some aphid‐pathogenic Entomophthorales is important for the seasonal pattern of their prevalence and survival but this process is poorly understood. To explore the possible mechanism involved in the process, Pandora nouryi (obligate aphid pathogen) interacted with green peach aphid Myzus persicae on cabbage leaves under favourable conditions. Host nymphs showered with primary conidia of an isolate (LC 50 : 0.9–6.7 conidia mm −2 4–7 days post shower) from air captures in the low‐latitude plateau of China produced resting spores (azygospores), primary conidia or both spore types. Surprisingly, the proportion of mycosed cadavers forming resting spores ( P cfrs ) increased sharply within the concentrations ( C ) of 28–240 conidia mm −2 , retained high levels at 240–1760, but was zero or extremely low at 0.3–16. The P cfrs – C relationship fit well the logistic equation P cfrs = 0.6774/[1 + exp(3.1229–0.0270 C )] ( r 2 = 0.975). This clarified for the first time the dependence of in vivo resting spore formation of P. nouryi upon the concentration of infective inoculum. A hypothesis is thus proposed that some sort of biochemical signals may exist in the host–pathogen interaction so that the fungal pathogen perceives the signals for prompt response to forthcoming host‐density changes by either producing conidia for infecting available hosts or forming resting spores for surviving host absence in situ .